Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Cynthia Samples, December 20, 1987 - Samples, Cynthiaet al (1987)
Iowa Christmas bird counts of regular and uncommon species found in Lake Red Rock contributed by Cynthia Samples, December 20, 1987. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1987-1988. Epson - sheet feed